Histological Study on the Development of Digestive System in Zoeal Stages of Mud Crab (Scylla olivacea) - Pattanee Jantrarotai,; Nopparat Srakaew,; Anong Sawanyatiputi, (Agriculture and Natural Resources, 2005)
Histological study of the digestive system was conducted in the zoeal stages (zoea 1- zoea5) of mud crabs (Scylla olivacea). The results showed that the digestive system of zoeae could be divided into three parts; foregut, midgut and hindgut. For the foregut, the gastric mill was not present in the cardiac stomach. The gland filter, anterior midgut caeca and posterior midgut caeca were not developed in the first and the early second zoeal stage. However, in the third zoea stage, these structures were developed and progressively increased in the later zoeal stage. The midgut gland or hepatopancreas was developed throughout the zoeal stages (zoea 1- zoea 5). This result showed the complexity of hepatopancreas , the more branched and larger size of this structure were found in the later zoeal stage.